Impact of Physical Inactivity on Risk of Developing Cancer of the Uterine Cervix: A Case-Control Study. Issue 3 (July 2016) - Szender, James Brian; Cannioto, Rikki; Gulati, Nicolas R.; Schmitt, Kristina L.; Friel, Grace; Minlikeeva, Albina; Platek, Alexis; Gower, Emily H.; Nagy, Ryan; Khachatryan, Edgar; Mayor, Paul C.; Kasza, Karin A.; et al.
Abstract : Objective: In this study, we investigated whether physical inactivity was associated with risk of cervical cancer in women treated at an American cancer hospital. Methods: This case-control study included 128 patients with cervical cancer and 512 controls matched on age. Controls were women suspected of having but not ultimately diagnosed with a neoplasm. Physical inactivity was defined in accordance with the 2008 Physical Activity Guidelines for Americans. Thus, participants reporting, on average, no moderate or vigorous recreational physical activity were classified as inactive. Unconditional logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Results: Compared with noncancer controls, those with cervical cancer had significantly increased odds of reporting abstinence from recreational physical activity (OR, 2.43; 95% CI, 1.56–3.80). No association was noted between occupational-related physical inactivity and cervical cancer (OR, 0.88; 95% CI, 0.58–1.36). Conclusions: Our findings suggest that abstinence from regular recreational physical activity is associated with increased odds of cervical cancer. To our knowledge, this is the first US-based study examining these associations. Given the 2008 Physical Activity Guidelines for Americans, this study has identified yet another potential public health benefit to regular physical activity. Further investigation is needed using a larger sample and prospectively collected data to characterize dose of activity to mitigate risk and the optimal window of susceptibility. Abstract : Physical inactivity may increase a woman's risk of developing cervical cancer when compared with those women who are physically active.